2021
DOI: 10.1038/s43018-021-00247-z
|View full text |Cite
|
Sign up to set email alerts
|

Low neoantigen expression and poor T-cell priming underlie early immune escape in colorectal cancer

Abstract: Immune evasion is a hallmark of cancer, and therapies that restore immune surveillance have proven highly effective in cancers with high tumor mutation burden (TMB) (e.g., those with microsatellite instability (MSI)). Whether low TMB cancers, which are largely refractory to immunotherapy, harbor potentially immunogenic neoantigens remains unclear. Here, we show that tumors from all patients with microsatellite stable (MSS) colorectal cancer (CRC) express clonal predicted neoantigens despite low TMB. Unexpected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 80 publications
3
59
0
Order By: Relevance
“…In addition to issues of antigen access, CD8 + T cell function in the TME is dictated by both antigen affinity and abundance 37, 56, 57 . We found that the probability of T cell egress, as measured by CXCR4 and ACKR3 surface expression, was dependent on the strength of TCR stimulation, where low affinity antigen encounter (e.g., endogenous, self-antigens) was insufficient to promote retention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to issues of antigen access, CD8 + T cell function in the TME is dictated by both antigen affinity and abundance 37, 56, 57 . We found that the probability of T cell egress, as measured by CXCR4 and ACKR3 surface expression, was dependent on the strength of TCR stimulation, where low affinity antigen encounter (e.g., endogenous, self-antigens) was insufficient to promote retention.…”
Section: Discussionmentioning
confidence: 99%
“…While these neoantigens might be “confirmed” as immunogenic in ex vivo assays, they would be unlikely to instigate deep antitumor responses in vivo due to their lower clonality[6]. This provides additional impetus for considering the clonality of neoantigen expression in addition to transcript abundance writ large[2, 8, 30]. Our results quantify others’ findings that pre-treatment neoantigen clonality and quality affect ICI outcomes and caution against overreliance on confirmation of immunogenicity via ex vivo assays that cannot capture neoantigen clonality.…”
Section: Discussionmentioning
confidence: 99%
“…Differential net birth rates, however, are captured in our model through presentome-specific death rates among lineages within a tumor. On neoantigen expression, recent murine studies indicate that poor expression of clonal neoantigens can stunt anti-tumor immunity, supporting the need to represent expression levels with more granularity (i.e., as a continuous variable) [30]. We also did not consider genome doubling events, which cause greater expression of neoantigens developed prior to doubling [28].…”
Section: Discussionmentioning
confidence: 99%
“…35 A study by Westcott et al suggested that for patients with immune ignorance of clonal neoepitopes due to low level expression, therapeutic vaccination of neoepitopes may be able to trigger robust immune responses. 36 Clinical trials for personalized therapeutic neoepitope vaccines have demonstrated that T-cell immune responses were induced for only a subset of candidate neoepitopes. [8][9][10][11] Although almost all vaccine trials reported thus far selected candidates based on computational algorithms, one trial selected candidates based on in vitro T-cell response to candidate neoepitopes presented by bacteria.…”
Section: Discussionmentioning
confidence: 99%